Why not ask them? A systematic scoping review of research on dyadic teacher–student relationships as perceived by students with emotional and behavioral problems - Vösgen-Nordloh, Meike; Kulawiak, Pawel R.; Bolz, Tijs; Koomen, Helma M. Y.; Hennemann, Thomas; Leidig, Tatjana (Frontiers in Education, 2024)
IntroductionMeta-analytical findings indicate that high-quality dyadic teacher-student relationships (TSRs) can act as social protective factors against the development or persistence of emotional and behavioral problems (EBPs) by fostering students’ social-emotional and cognitive learning. However, previous research primarily focused on samples of students without EBPs and relied on teacher-rated TSRs. Research on dyadic TSRs from the perspective of students with EBPs is scarce, yet their self-perceptions could offer valuable insights into whether and how dyadic TSRs serve as protective factors for them. Therefore, this systematic scoping review is guided by the central question of how research on dyadic TSRs from the perspective of students with EBPs has been conducted and what insights have been gained to date.MethodsThis question is explored through a narrative synthesis of existing studies, thereby identifying current research approaches, empirical findings, practical implications, and future research needs. A database search using keywords related to EBPs and TSRs yielded 24 included studies.Results and discussionSynthesizing these studies reveals five overarching conclusions. First, students with EBPs and their teachers tend to experience dyadic TSRs less favorably than typically developed (TD) students and their teachers. Second, relationship-enhancing interventions focusing on either teacher-student interactions, contextual factors or individual characteristics of teachers and students appear to be effective for students with EBPs. Third, students with EBPs seem to perceive stronger positive affective relationships with their teachers than teachers do with them. Fourth, students with EBPs may perceive their dyadic TSRs as ambivalent, exhibiting both highly positive and highly negative aspects. Fifth, for the social–emotional and academic development of students with EBPs, dyadic TSR-quality seems to be a risk or protective factor, acting differently than in TD-student. However, due to the diverse nature of the included studies, these conclusions remain only preliminary. Consequently, the review concludes with 10 key recommendations that might guide future research on dyadic TSRs from the perspective of students with EBPs.